2012
DOI: 10.1080/03601234.2012.663613
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of homologous and heterologous formats in nanocolloidal gold-based immunoassays for parathion residue determination

Abstract: The effectiveness of homologous and heterologous formats in a nanocolloidal gold-based immunoassay for pesticide residue determination was investigated. Parathion, one of the most toxic organophosphorus pesticides, was used as the target analyte. One-step homologous and heterologous test strips based on a nanocolloidal gold-labeled monoclonal antibody were developed for the rapid detection of parathion residues. The results showed that the heterologous format was more effective than the homologous format, bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The design and synthesis of haptens is a critical step in immunoassay development. The literature data show that the most sensitive competitive immunoassays are those developed when the coating antigen is different from the immunizing antigen (heterologous assay). Not only the carrier protein but also at least the handle should be different, and preferably, the chemical structure of the hapten should be modified. The smaller the hapten, the more important hapten design becomes.…”
Section: Resultsmentioning
confidence: 99%
“…The design and synthesis of haptens is a critical step in immunoassay development. The literature data show that the most sensitive competitive immunoassays are those developed when the coating antigen is different from the immunizing antigen (heterologous assay). Not only the carrier protein but also at least the handle should be different, and preferably, the chemical structure of the hapten should be modified. The smaller the hapten, the more important hapten design becomes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of publications have shown that in competitive immunoassays the sensitivity of the assay is greatly increased when the hapten in the coating antigen is different from the immunogen. , Therefore, additional haptens were used in the development of heterologous immunoassays (haptens 5 and 6 ). Fipronil analogue, compound 2 (Scheme ), and 2,6-dichloro-4-(trifluoromethyl)­aniline were attached to protein without additional modification through the amine group.…”
Section: Resultsmentioning
confidence: 99%
“…Since the methodin development was a competitive immunoassay, its sensitivity was influenced by several well-known factors, such as antibody dilution and competitor concentration, provided that a definite antiserum was used. Additional factors that could be considered were: the chemical structure of the hapten (actually, the use of heterologous competitors had been shown to improve sensitivity [67]), the structure of the antigen used as the competitor in the assay (as far as the nature of the carrier-protein and the degree of conjugation between the hapten and the carrier-protein itself were considered); the specific response of the reporter used to label the antibody; the extent of antibody labelling (moles of reporter per mole of antibody). In effect, the work of Byzovaet al [68] firstly reported the effect of varying some of the described factors on LFIA performances and, in particular, showed that the diminishing of the molar substitution ratio (SR) between the hapten and the carrier-protein in the preparation of the competitor significantly improved as say sensitivity.…”
Section: Development Of a Highly Sensitive Lfia For Measuring Afm 1 Imentioning
confidence: 99%